Security education as part of the fight against aggression - Czura, Tomasz; Sapiński , Aleksander (Scientific Journal of Bielsko-Biala School of Finance and Law, 2020)
The presented article is an attempt to show the application of Positive Discipline in solving the problem of aggression among children and young people. The author presents the definition, sources, forms of aggression and refers to the ICD-10 classification. Further on, the article presents the method of Positive Discipline, which, according to the author, can contribute to the reduction of aggression among the young generation. These principles were introduced to psychology by Alfred Adler. Then they were applied in the Positive Discipline method developed by Jane Nelsen. The author not only presented the possibility of using modern educational methods to combat the threats of the modern world, but also made a substantive assessment of one of these methods. It is the Positive Discipline, which meets the necessary criteria to effectively reduce aggression among children and youth.